2019
DOI: 10.12991/jrp.2019.158
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetic activity and mineral elements evaluation of Vernonia amygdalina leaves obtained from Malaysia

Abstract: Diabetes has been characterized by transmuted lipids, hyperglycemia, proteins, and carbohydrates metabolism that can affect the quality of life. Although there are quite several synthetic drugs used in managing this disease, however, due to their side effects, the use of natural sources is imperative. This study focused on the in-vitro inhibitory activity of Vernonia amygdalina leaf grown in Malaysia using both α-amylase and α-glucosidase assays. The quantities of mineral elements in the plant extracts through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…However, Yuan et al [52] reported better α-amylase activity with microwave-assisted extraction compared to conventional fractions. Alara and Abdurahman, [53] reported significant differences between the extracts when using the Soxhlet and optimized MAE extraction techniques. They further observed that the extracts obtained via optimized MAE had the highest activity.…”
Section: Alpha-amylase Inhibitory Activitymentioning
confidence: 99%
“…However, Yuan et al [52] reported better α-amylase activity with microwave-assisted extraction compared to conventional fractions. Alara and Abdurahman, [53] reported significant differences between the extracts when using the Soxhlet and optimized MAE extraction techniques. They further observed that the extracts obtained via optimized MAE had the highest activity.…”
Section: Alpha-amylase Inhibitory Activitymentioning
confidence: 99%
“…In other studies, Vernonia amygdalina leaves were also shown to have the potential as a natural source for managing diabetes. In vitro, the extract of this plant was proven to contain a lot of mineral elements (potassium, magnesium, and calcium) and a little content of chromium through the microwave-assisted extraction method [10].…”
Section: ■ Introductionmentioning
confidence: 99%